السياحة الإلكترونية ودورها في تحقيق التميز السياحي: دراسة استطلاعية لآراء المديرين في عدد من المنظمات السياحية في محافظة دهوك - أوسو، خيري علي; عمر، بيمان عبدالقادر; أولاد إبراهيم، ليلى (جامعة صلاح الدين, 2017)
يهدف البحث الى دراسة السياحة الالكترونية ودورها في تحقيق التميز السياحي في عدد من المنظمات السياحية في محافظة دهوك، منطلقا من مخطط فرضي ياخذ بنظر الاعتبار اتجاه العلاقة بين السياحة الالكترونية وتحقيق التميز السياحي، وتحقيقا لهدف البحث واكمال متطلباته باشر الباحث باعداد اطار نظري بالافادة من ادبيات الموضوع ، واعتمد البحث المنهج الوصفي التحليلي ، وتم استخدام الاستبانة لاستطلاع اراء عينة البحث ، والمكونة من المديرين في عدد من المنظمات السياحية والذين بلغ عددهم (60) مديرا ، وتم استخدام بعض الأساليب الإحصائية لتحليل النتائج واختبار الفرضيات، تمثلت اهم الاستنتاجات باستخدام المنظمات المبحوثة للسياحة الالكترونية، وتحقيقها للتميز السياحي، وتوصل البحث الى مجموعة من المقترحات من أهمها تعزيز استخدام السياحة الالكترونية، وتعزيز التميز السياحي، وإزالة العقبات التي تعيق تعزيز المتغيرين.
The study aims at studying the electronic tourism and also its role in achieving the tourism differentiation in many tourism organizations in Duhok province. The study has initiated a hypothetical diagram which takes into consideration the direction of the relationship between the electronic tourism and achieving the tourism differentiation, and in order to fulfill the goal of the study and also accomplishing all its requirements, the researcher started to prepare a theoretical frame making advantage of the subject's literature, and also the analytical descriptive analysis was adopted, a questionnaire was used to make the survey of the ideas of the investigated samples that consists of (60) managers. Some statistical means were used to analyze the results and test the hypotheses. The most important conclusions were represented in the usage of the electronic tourism by the surveyed organizations and, thus, achieved the tourism excellence. Many recommendations were obtained and concluded by the research some of those recommendations were to consolidate and support the usage of the electronic tourism and also supporting and backing the tourism differentiation and also eliminating the obstacles that hamper the reinforcement of those variables.
Keywords: السياحة الإلكترونية -- تكنولوجيا المعلومات -- المنظمات السياحية -- التميز السياحي